A posture monitoring system with IMU for ophthalmologist while operating the slit lamp - Kian Sek Tee; Eugene Low; Wellesly Tony; Safinaz Binti Mohd Khialdin; Jaysuman Bin Pusppanathan; Chin Fhong Soon; Toong Hai Sam (Institute of Advanced Engineering and Science, 2020)
The posture monitoring system monitors the posture changes of the upper body and the spinal cord applying to ophthalmologists while operating the slit lamp. The motivation to the pursuit of this system is to relate posture changes while in a static sitting posture to the spinal deviation from the g-line. Often times, the spinal deviation from the g-line is classified as bad posture because of the shift in weight distribution on the spine causing pain and discomfort in certain areas of the spine. This paper presents the design concept, the development process and the working principle of the posture monitoring system using Inertial Measurement Unit (IMU) sensor. The raw measurement data obtained from human trials is tabulated and converted into a graphical representation in which all postures can be identified and distinguished by referring the relative wave pattern. The procedure is important in the improvement on the posture monitoring system for the human trials on the ophthalmologist in future.